Neorickettsia sennetsu as a Neglected Cause of Fever in South-East Asia. - Sabine Dittrich; Weerawat Phuklia; Gareth D H Turner; Sayaphet Rattanavong; Vilada Chansamouth; Stephen J Dumler; David J P Ferguson; Daniel H Paris; Paul N Newton (Public Library of Science (PLoS), 2015)
Neorickettsia sennetsu infection is rarely recognized, with less than 100 globally reported patients over the last 50 years. The disease is thought to be contracted by eating raw fish, a staple of many South-East Asian cuisines. In 2009, the first patient with sennetsu was identified in the Lao PDR (Laos), raising the question as to how common this organism and related species are in patients presenting with fever. We investigated the frequency of N. sennetsu infection at hospitals in diverse areas of Laos. Consenting febrile hospital inpatients from central (Vientiane: n = 1,013), northern (Luang Namtha: n = 453) and southern (Salavan: n = 171) Laos were screened by PCR for N. sennetsu, if no previous positive direct diagnostic test was available. A PCR-restriction fragment length polymorphism assay was developed to differentiate between N. sennetsu, Ehrlichia chaffeensis and Anaplasma phagocytophilum. To allow more detailed studies of N. sennetsu, culture was successfully established using a reference strain (ATCC VR-367), identifying a canine-macrophage cell line (DH82) to be most suitable to visually identify infection. After screening, N. sennetsu was identified and sequence confirmed in four (4/1,637; 0.2%) Lao patients. Despite the previously identified high seroprevalence of N. sennetsu antibodies in the Lao population (~17%), acute N. sennetsu infection with sufficient clinical signs to prompt hospitalization appears to be rare. The reservoir, zoonotic cycle and pathogenicity of N. sennetsu remain unclear and require further investigations.